2017
DOI: 10.1016/j.triboint.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the plasticity accumulation of Ti-6Al-4V fretting wear by decoupling the effects of wear and surface profile in finite element modelling

Abstract: A finite-element-based wear modelling methodology and a computational device for decoupling wear effects is presented in this study. The decoupling of wear effects facilitates the capture of plasticity accumulation on a particular wear-scarring profile after a specific number of cycles. It was determined that significant plasticity accumulation due to plastic shakedown was predicted in a partial-slip case, while a saturation of plastic deformation was predicted in a gross-sliding case. It was also predicted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The mesh refinement showed convergence towards the peak analytical solution for the shear traction. Finally, according to the results, a 2 µ m × 2 µ m element size is used around the contact zone, which is smaller than in most of the previous numerical studies [8,[32][33][34][35][36][37][38]. The simulation results and the theoretical results may not be exactly the same, due to numerical errors and geometric constraints [67].…”
Section: Finite Element Model and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesh refinement showed convergence towards the peak analytical solution for the shear traction. Finally, according to the results, a 2 µ m × 2 µ m element size is used around the contact zone, which is smaller than in most of the previous numerical studies [8,[32][33][34][35][36][37][38]. The simulation results and the theoretical results may not be exactly the same, due to numerical errors and geometric constraints [67].…”
Section: Finite Element Model and Validationmentioning
confidence: 99%
“…For experimental methods, it is difficult to get the details of stress field and initiation of crack. Therefore, numerical modeling is an efficient way to solve the problem of fretting fatigue [8,[32][33][34][35][36][37][38] and fracture [39][40][41][42][43]. However, only few studies have taken into account the heterogeneity of material under fretting fatigue conditions [14,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the peak value cannot be reached again when the cylinder moves to the far-right side of contact unless the relative slip amplitude is much greater than the contact zone. This phenomenon is explained in [37,38]. Another interesting phenomenon is that the plasticity decreases with the number of cycles, and the plastic strain on both tailing and leading edges increases with the number of cycles.…”
Section: Flat Specimenmentioning
confidence: 88%
“…Materials 2021, 14, x FOR PEER REVIEW 11 of much greater than the contact zone. This phenomenon is explained in [37,38]. Anoth interesting phenomenon is that the plasticity decreases with the number of cycles, and t plastic strain on both tailing and leading edges increases with the number of cycles.…”
Section: Flat Specimenmentioning
confidence: 95%
“…In the study of Mohd et al [Mohd Tobi, Ding, Bandak et al (2009)], the evolution of plastic variables and effects of plasticity during fretting wear were analyzed using a kinematic hardening plasticity model for the cyclic plasticity behaviour description. Mohd et al also investigated the accumulation of plastic strain in fretting wear decoupling wear effects [Mohd Tobi, Sun and Shipway (2017)]. Predicted results showed that significant plasticity accumulation existed due to plastic shakedown in the partial slip condition, while a saturation of plastic deformation occurs under gross sliding condition.…”
Section: Neglecting Debris Effectsmentioning
confidence: 99%